The effect of nitrogen monoxide donors on the indexes of cadmium-induced oxidative stress in different rat tissues - Nikitchenko, I.; Rybalchenko, T.; Barannik, T.; Pavychenko, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
Oxidative stress is considered to be the main mechanism of cadmium ions toxic effect on the cells and is caused by cadmium, as a non-transition metal, indirectly. Oxidative damage to cells due to the action of cadmium ions is tissue-specific and is associated with the antioxidant system inhibition, free heme accumulation and essential metals substitution in metalloproteins. Nitrogen monoxide (NO) exhibits high affinity for heme and proteins and peptides sulfhydryl groups, known to be the main molecular targets for cadmium ions. Taking all the above-mentioned into account, the aim of this work was to study the effect of NO radicals donors on the prooxidant-antioxidant state of mammalian tissues under oxidative stress caused by cadmium chloride administration in vivo. Male Wistar rats weighing 160–200 g were used in the study. CdCl2 was administered subcutaneously at a dose of 14 mg/kg body weight. The direct donor of the NO radical sodium nitroprusside (SNP, 1 mg/kg mass) and the substrate of the NO synthase reaction L-arginine (600 mg/kg mass) were administered intraperitoneally. In order to study the corrective action, donors of the NO radical were injected 0.5 h before the cadmium salt. The objects of investigation were blood plasma and liver, kidneys and spleen homogenates of rats. The cadmium chloride treatment caused a number of prooxidant-antioxidant balance disorders, most of which were revealed a day after injection. The accumulation of lipid peroxidation products was found in rat serum, liver, and spleen. The enhancement of prooxidant processes in these tissues may originate from cadmium ions and hemolysis products entry. In the antioxidant system, significant changes were observed under cadmium action only in the liver: an increase in the reduced glutathione content and SOD activity and a decrease in catalase activity. The precursor of nitric oxide L-arginine did not change the basal level of prooxidant-antioxidant parameters, and in most cases did not affect their dynamics in the organs studied after cadmium chloride administration. A direct NO donor, sodium nitroprusside, acted in liver and spleen mostly as a prooxidant. In liver, the injection of only nitroprusside, as well as the combined administration of SNP and CdCl2, led to free radical processes activation just in two hours. In spleen, the combined treatment by SNP and cadmium salt also caused an earlier development of oxidative stress, as witnessed by an increase in lipid hydroperoxides level and a decrease in reduced glutathione content. Therefore, the injection of a direct NO donor, sodium nitroprusside, and a substrate of NO synthase, L-arginine, in selected doses has insignificant corrective action on cadmium-induced oxidative stress in the liver, kidneys and spleen. However, in blood both donors of NO effectively prevented the accumulation of lipid peroxidation products under CdCl2 treatment; in addition, L-arginine significantly reduced the lactate dehydrogenase release, which may indicate blood cells and blood vessels protection from the damage caused by cadmium ions.